Enhancing sonocatalytic properties of TiO2 nanocatalysts by controlling the surface conditions: effect of particle size and PVA modification. Issue 58 (13th December 2016) - Soleimani, Foad; Madaah Hosseini, Hamid Reza; Ordikhani, Farideh; Mokhtari-Dizaji, Manijhe
Abstract: The influence of particle size and surface modification on sonocatalytic activity of TiO2 nanoparticles was investigated by measuring the degradation efficiency of methyl orange (MO) as a model pollutant. Crystalline TiO2 nanoparticles with different particles and aggregate size were prepared through solution-phase method with varying synthesis temperatures. Coating with polyvinyl alcohol was performed to enhance colloidal stability of the particles over a wide range of pH values (1.5–7.5). Characterization was carried out using X-ray diffraction, high-resolution transmission electron microscopy, dynamic light scattering, and Fourier-transformed infrared techniques. It was found that sonodegradation of MO decreased as the synthesis temperature increased. Moreover, sonoactivity of the modified nanoparticles improved because polymeric coating inhibited particles collision and also their growth due to sonication-induced Ostwald ripening mechanism.